Fritid, frihet og fellesskap Kunnskap og løsninger i lokalt kulturarbeid blant barn og unge - Hylland, Ole Marius (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2019)
This book is about possibilities for, challenges for and knowledge about local cultural work among young people. It describes cultural work at a municipal level but shows also how this work is aiming to reach goals that it has in common with national cultural policy: quality, participation, inclusion, diversity and democracy. Using the municipality and town of Drammen as a vantage point, the book investigates how different parameters effect local cultural work, and how cultural policy at a municipal level is, by necessity, pragmatic, practical and sometimes prosaic. This topic is dealt with through a combination of qualitative and quantitative analysis. The empirical data presented and discussed in the book is a combination of qualitative case studies and quantitative survey data. The survey data shows variations and patterns in the cultural consumption of an age cohort in the municipality, and the case studies show different ways of effectuating and organizing cultural work at this level. Finally, the book discusses the complex interplay between means and ends when a municipality is working to make culture matter for young people.